Comparison of Composition and Nutritional Characteristics of Sweet Sorghum (Sorghum bicolor L. Moench) and Commercial Vinegars to Aid Their Utilization - Eggleston, Gillian; Teixeira, Vitor [UNESP]; Aita, Giovanna; Triplett, Alexa; Verret, Chardcie; Foster, Tyrennee; St. Cyr, Eldwin; Heckemeyer, Matthew (Springer Nature, 2024)
Food, specialty (gourmet), and cleaning (produced in large volume) vinegars, and even flavored drinking vinegars are growing fast in popularity. The physico-chemical properties of light and dark sweet sorghum (grass) vinegars manufactured from juice or diluted syrup, respectively, were compared to sixteen commercial vinegars from fruit (red and white wine, balsamic, apple cider), cereal (rice, malt) and grass (sugarcane). Brix of all the vinegars varied greatly from 3.3 to 28.6%; sweet sorghum vinegars ranged from 9.4 to 10.9%. Vinegars manufactured from particulate juices had higher turbidity values compared to those from diluted syrups. Color indicator values (color at pH 9.0/color at pH 4.0) were not an indication of phenolic colorants in the vinegars. Dark sweet sorghum vinegar contained the greatest (P < 0.05) total phenolic content (2617 mg/L). The predominant phenolic components in the vinegars were phenolic acids with only one flavonoid (catechin) detected. Sinapic acid was the major phenolic acid in many vinegars and sweet sorghum vinegars contained > 360 ug/g. Only the sweet sorghum vinegars contained aconitic acid (cis form) (av. 1078 µg/g) and relatively high levels of citric (77 µg/g) and iso-citric acids (av. 443 µg/g). All vinegars exhibited low antioxidant 2,2-diphenyl-1-picryl hydrazyl (DPPH) radical scavenging activities and oxygen radical absorbance capacity (ORAC) values, with acceptable values for sweet sorghum vinegars, but red wine vinegars exhibited the highest values. Overall, sweet sorghum vinegar produced from diluted syrup had higher nutritional value than vinegar from juice and were, generally, in the same range as balsamic and red wine vinegars.
Keywords: Bioactives; Color; Commercial vinegars; Organic acids; Phenolic compounds; Sweet sorghum